(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Cereals and pulses are inexpensive and sustainable sources of nutrients, minerals, and nutraceutical compounds. The deprived consumption of these cereals and pulses in native form is not successful. Hence development of ready-to-cook (RTC) blended formulations based on cereals and pulses will impede the use of these ingredients for balanced nutrition in our day-to-day foods. Accordingly in the present study, we selected five (5) different cereals and pulses, i.e., barley, finger millet, chickpeas, green gram, and horse gram, along with unripe banana, and arrowroot powder, for the development of RTC food formulations. Initially nine (9) combinations of RTC formulations were prepared and evaluated for its sensorial acceptance. Further, the optimized formulation was packed and stored at three different storage conditions